2020
DOI: 10.1186/s13287-019-1538-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mesenchymal stem cells in animal models of lupus nephritis: a meta-analysis

Abstract: Background: Lupus nephritis is usually manifested by proteinuria, active urinary sediment, hypertension, and renal failure and is a serious complication with more than 50% occurrence in systemic lupus erythematosus patients. Mesenchymal stem cells (MSC) present remarkable immunomodulatory ability, and these cells are potential therapeutic agents for autoimmune disorders. In clinical trials, the effectiveness of MSC in the treatment of lupus nephritis is still controversial. A meta-analysis was performed to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…We also found that MSCs group had lower UAE than the control group. In previous, MSCs treatment can reduce the levels of Scr, BUN, proteinuria in lupus nephritis in mice 37 . Chen et al 38 Furthermore, our study indicated that the MSCs treatment can alleviate the in ammatory cells, necrotic tubule, regenerative tubules, renal interstitial brosis in kidney disease induced by toxicant.…”
Section: Discussionmentioning
confidence: 89%
“…We also found that MSCs group had lower UAE than the control group. In previous, MSCs treatment can reduce the levels of Scr, BUN, proteinuria in lupus nephritis in mice 37 . Chen et al 38 Furthermore, our study indicated that the MSCs treatment can alleviate the in ammatory cells, necrotic tubule, regenerative tubules, renal interstitial brosis in kidney disease induced by toxicant.…”
Section: Discussionmentioning
confidence: 89%
“…We also found that MSCs group had lower UAE than the control group. In previous, MSCs treatment can reduce the levels of Scr, BUN, proteinuria in lupus nephritis in mice [37]. Chen et al [38] found that MSCs have ameliorated ischemia/reperfusion injury-induced acute kidney injury in rats and can reduce the Scr levels.…”
Section: Discussionmentioning
confidence: 94%
“…Genetically induced MSC dysfunction has been correlated with SLE disease ( 65 ). Further this therapeutic model of allogenic transplantation of MSCs reduces pathologies associated with SLE ( 66 ). Our studies also show a decrease in number and clonability of these cells in MRL -lpr mice.…”
Section: Discussionmentioning
confidence: 99%